2003
DOI: 10.2486/indhealth.41.55
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Occupational Exposures on Male Fertility: Literature Review

Abstract: The present review was aimed to determine the influence of working conditions, occupational exposures to potential chemical and physical reproductive toxic agents and psychological stress during work on male fertility. Significant associations were reported between impaired semen parameters and the following chemical exposures: metals (lead, mercury), pesticides (dibromochlorophane, 2,4-dichlorophenoxyacetic acid), ethylene glycol ethers and estrogens. The following physical exposures were shown to deteriorate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
3
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(100 citation statements)
references
References 50 publications
(49 reference statements)
5
88
3
4
Order By: Relevance
“…In 1995 the US Institute of Medicine Committee stated that "the prevailing view is that exposure of the human male to chemicals and ionizing radiation is generally unrelated to the occurrence of developmental endpoints such as miscarriage, birth defects, growth retardation and Table 1. Chemical and physical exposures that have been associated with reduced semen quality or impaired male fertility (for systematic reviews, see [15][16][17][18][19][20][21][22][23][24][25][26] npg cancer" [56]. The question is, however, whether lack of convincing examples of male mediated developmental toxicity in humans is due to the non-existence of this phenomenon due to huge methodological challenges in demonstrating effects.…”
Section: Male Mediated Development Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…In 1995 the US Institute of Medicine Committee stated that "the prevailing view is that exposure of the human male to chemicals and ionizing radiation is generally unrelated to the occurrence of developmental endpoints such as miscarriage, birth defects, growth retardation and Table 1. Chemical and physical exposures that have been associated with reduced semen quality or impaired male fertility (for systematic reviews, see [15][16][17][18][19][20][21][22][23][24][25][26] npg cancer" [56]. The question is, however, whether lack of convincing examples of male mediated developmental toxicity in humans is due to the non-existence of this phenomenon due to huge methodological challenges in demonstrating effects.…”
Section: Male Mediated Development Toxicitymentioning
confidence: 99%
“…Although the sitting position may cause increase of scrotal temperature, this increase seems not strong enough to disrupt spermatogenesis that may recover during other parts of the day [13,14]. Research during past 25 years has identified a large number of chemicals and occupational exposures that may impair male fertility (Table 1) [15][16][17][18][19][20][21][22][23][24][25][26]. It should, however, be acknowledged that epidemiological studies of male fertility and semen quality are beset with a number of pitfalls and methodological limitations crude exposure assessment, low participation rates, inadequate study size and lacking quality assurance of the semen analysis [27,28].…”
Section: Occupational Hazardsmentioning
confidence: 99%
“…Occupational activities involving exposure to specific chemicals or expositions to toxicants may impair male reproductive health and cause infertility in humans [27,37,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…Many jobs that require heavy daily computer use have been found to be stressful (Carajon, 1993;Mocci et al, 2001) and stress is a risk factor of infertility (Sheiner et al, 2003). Also, prolonged sitting in front of VDT may affect semen quality through increasing temperature of the testes (De Fleurian et al, 2009).…”
Section: Disccusionmentioning
confidence: 99%